Molecular Characterization and Expression Profiling of Brachypodium distachyon L. Cystatin Genes Reveal High Evolutionary Conservation and Functional Divergence in Response to Abiotic Stress - Subburaj, Saminathan; Zhu, Dong; Li, Xiaohui; Hu, Yingkao; Yan, Yueming (Frontiers in Plant Science, 2017)
ABSTRACT Cystatin is a class of proteins mainly involved in cysteine protease inhibition and plant growth and development, as well as tolerance under various abiotic stresses. In this study, we performed the first comprehensive analysis of the molecular characterization and expression profiling in response to various abiotic stresses of the cystatin gene family in Brachypodium distachyon, a novel model plant for Triticum species with huge genomes. Comprehensive searches of the Brachypodium genome database identified 25 B. distachyon cystatin (BdC) genes that are distributed unevenly on chromosomes; of these, nine and two were involved in tandem and segmental duplication events, respectively. All BdC genes had similar exon/intron structural organization, with three conserved motifs similar to those from other plant species, indicating their high evolutionary conservation. Expression profiling of 10 typical BdC genes revealed ubiquitous expression in different organs at varying expression levels. BdC gene expression in seedling leaves was particularly highly induced by various abiotic stresses, including the plant hormone abscisic acid and various environmental cues (cold, H2O2, CdCl2, salt, and drought). Interestingly, most BdC genes were significantly upregulated under multiple abiotic stresses, including BdC15 under all stresses, BdC7-2 and BdC10 under five stresses, and BdC7-1, BdC2-1, BdC14, and BdC12 under four stresses. The putative metabolic pathways of cytastin genes in response to various abiotic stresses mainly involve the aberrant protein degradation pathway and reactive oxygen species (ROS)-triggered programmed cell death signaling pathways. These observations provide a better understanding of the structural and functional characteristics of the plant cystatin gene family